2004
DOI: 10.1002/pri.311
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation: analysis of a clinical service

Abstract: Clinical pulmonary rehabilitation programmes are effective for most patients. However for patients with more severe impairment, maximal gains may be harder, or take longer, to achieve. Patients with restrictive disease appear to do well, although future trials will be needed to test this supposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…15,16,18,25 Views of participants who had not been groomed by prior information about PR are important contributors to the range of views about the feasibility and acceptability of PR to COPD patients. Themes identified in this research as obstacles to participation in PR not previously identified in the systematic review of Keating et al include the role of experienced patients (lay health workers), difficulties in prioritising the treatment, contrary beliefs about the role and safety of exercise, and fears about criticism, exposure and inadequacy.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…15,16,18,25 Views of participants who had not been groomed by prior information about PR are important contributors to the range of views about the feasibility and acceptability of PR to COPD patients. Themes identified in this research as obstacles to participation in PR not previously identified in the systematic review of Keating et al include the role of experienced patients (lay health workers), difficulties in prioritising the treatment, contrary beliefs about the role and safety of exercise, and fears about criticism, exposure and inadequacy.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…This requires consensus about the key performance measures of PR services. To date, changes in exercise performance and health status are often used to qualify individuals with COPD as responders or non-responders to PR [5][6][7][8][9][10]. Nevertheless, changes in the abovementioned outcomes following PR are mostly differential.…”
Section: Introductionmentioning
confidence: 99%
“…Przeprowadzone badania pozwoli艂y oceni膰 wiedz臋 badanych student贸w z zakresu fizjoterapii oddechowej, kt贸ra jest niezb臋dna w pracy piel臋gniarskiej do prawid艂owej opieki nad pacjentem, a zw艂aszcza nad pacjentem unieruchomionym ze wzgl臋du na fakt, i偶 to piel臋gniarka jest osob膮 kt贸ra sprawuje ca艂o-dobow膮 opiek臋 nad pacjentem, co jest zgodne z badaniami Garrod i wsp. [9,10].…”
Section: Dyskusjaunclassified
“…Fakt ten znajduje odzwierciedlenie w wielu pozycjach 艣wiatowego pi艣miennictwa [9][10][11][17][18][19][20]. WNIOSKI 1.…”
unclassified